HUBUNGAN ANTARA KEPRIBADIAN HARDINESS DAN ACADEMIC BURNOUT PADA MAHASISWA YANG MENJALANI PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 - Anantya Putri, Aisyah (Psikologi UHAMKA, 2022)
The COVID-19 pandemic demands many changes, including the implementation of an online learning system. This situation adds to the pressure thus increasing the occurrence of academic burnout. Academic burnout is a feeling of tiredness experienced by individuals when faced with various kinds of excessive demands, has an uninterested attitude towards the tasks given in lectures, and has a feeling that he is incompetent as a student. This study uses a quantitative approach, aiming to determine the relationship between personality hardiness and academic burnout in students undergoing online learning during the COVID-19 pandemic. This study involved 55 male and female student respondents from a number of universities in Jakarta who were currently undergoing or had undergone online learning during the COVID-19 pandemic using a purposive sampling technique. Methods of data collection using a questionnaire. The scale used to measure the hardiness personality variable is the Dispositional Resilience Scale (DRS-15) developed by Hystad et.al (2010) (α = .725), and the academic burnout variable is measured using the Maslach Burnout Inventory - Student Survey (MBI-SS). ) by Schaufeli, et al (2007) (α = .880). Based on the results of data analysis using Pearson correlation, it shows that there is a significant negative relationship between personality hardiness and academic burnout in students undergoing online learning during the COVID-19 pandemic with a correlation coefficient value of -0,288 (p = 0,033). This means that the higher the hardiness personality, the lower the academic burnout, and vice versa. Thus, this study accepts the alternative hypothesis (Ha) and rejects the null hypothesis (H0). Theoretically, it is hoped that this research will contribute to science in the field of educational psychology regarding hardiness personality and academic burnout for students during the pandemic, especially in Jakarta. Meanwhile, practically it is hoped that it can help students who are vulnerable to academic burnout and are undergoing online learning during the COVID-19 pandemic to be able to develop a hardiness personality to avoid academic burnout.